Validity of the HIV disability questionnaire for people living with human immunodeficiency virus in South Africa - Adeleke, Adetunji Abiodun (My University, 2017)
Background and purpose Disability in people living with human immunodeficiency virus (HIV) has become a major health problem especially in HIV endemic countries like South Africa. In this study we determined the validity and reliability of the first specific disability assessment instrument for people living with HIV, the HIV Disability Questionnaire (HDQ). Methodology Adults living with HIV were recruited from hospital clinics and AIDS service organizations in South Africa. A demographic questionnaire and HDQ paired with two reference measures were administered. To assess construct validity, factor analysis, convergent and divergent validity and level of disability against known group variables were determined. Cronbach’s alpha was established to determine reliability of the HDQ. Results Of the 498 participants, the majority were females (68.27%) and were taking antiretroviral therapy (100%). Majority of the participants were black (95.18%) and have a median age of 41 years. Confirmatory factor analyses indicated goodness of fit similar to that previously shown for the HDQ, with the hypotheses for convergent and divergent validity and known group variables being accepted. Internal consistency was good with Cronbach’s alpha values above 0.7 for all domains on the HDQ. Conclusions The HDQ demonstrates a variable degree of construct validity and internal consistency when administered to adults living with HIV in South Africa.
A dissertation submitted to the Faculty of Health Sciences, University of the Witwatersrand, in fulfillment of the requirements for the degree of Master of Science in Occupational Therapy. Johannesburg, January 2017
Keywords: HIV Disability